2011
DOI: 10.1007/s00253-011-3237-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genes that impact on aroma profiles produced by Saccharomyces cerevisiae and the production of higher alcohols

Abstract: During alcoholic fermentation, many volatile aroma compounds are formed by Saccharomyces cerevisiae, including esters, fatty acids, and higher alcohols. While the metabolic network that leads to the formation of these compounds is reasonably well mapped, surprisingly little is known about specific enzymes involved in specific reactions, the regulation of the network, and the physiological roles of individual pathways within the network. Furthermore, different yeast strains tend to produce significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 75 publications
(89 reference statements)
1
51
0
Order By: Relevance
“…Moreover, the most important flavour and aroma compounds formed from amino acids are higher alcohols and their associated esters and volatile acids. The presence of skins during fermentation could have favoured the availability of different aromaprecursor amino acids, therefore influencing the wine's final volatile composition (Styger et al, 2011). In addition, the presence in skin contact wines of higher available assimilable nitrogen levels could influence yeast CO 2 production, which also might cause an important volatilisation with CO 2 evolution during fermentation (Dennis et al, 2012).…”
Section: Effect Of Skin Contact On the Chemical And Sensory Profile Omentioning
confidence: 99%
“…Moreover, the most important flavour and aroma compounds formed from amino acids are higher alcohols and their associated esters and volatile acids. The presence of skins during fermentation could have favoured the availability of different aromaprecursor amino acids, therefore influencing the wine's final volatile composition (Styger et al, 2011). In addition, the presence in skin contact wines of higher available assimilable nitrogen levels could influence yeast CO 2 production, which also might cause an important volatilisation with CO 2 evolution during fermentation (Dennis et al, 2012).…”
Section: Effect Of Skin Contact On the Chemical And Sensory Profile Omentioning
confidence: 99%
“…1. Previous studies have shown that metabolic perturbation derived from mutation of genes associated with the biosynthesis and degradation pathways of leucine, isoleucine, and valine in yeast can improve C4~C5 higher alcohol yield based on these two pathways242526. Mutating acetohydroxyacid synthase (AHAS) gene responsible for transforming pyruvic acid into α-acetolactic acid can reduce the generation of the diacetyl, thereby improving the production of higher alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory analysis confirmed that the overexpression of BAT1 and BAT2 had an impact on aroma profiles of wines and distillates (Lilly et al 2006b). The perturbation of the BAT genes not only affects the concentrations of metabolites directly linked to these genes, but also other aroma metabolites not directly related to higher alcohols, highlighting the complexities of the interconnections within such complex metabolic networks (Lilly et al 2006b; Styger et al 2011a). BAT2 seems to have a more prominent role than BAT1 in the Ehrlich pathway.…”
Section: Recent Advances In Knowledge Of Flavour Compound Formation Bmentioning
confidence: 99%
“…To date, five proteins have been implicated in α-keto decarboxylation: the pyruvate decarboxylases Pdc1p, Pdcp5 , and Pdc6p; the phenylpyruvate decarboxylase Aro10p; and the probable carboxylase Thi3p (Styger et al 2011a), which plays a role as a regulatory protein of the enzymes involved in thiamine biosynthesis (Mojzita and Hohmann 2006; Nosaka et al 2005). …”
Section: Recent Advances In Knowledge Of Flavour Compound Formation Bmentioning
confidence: 99%